Real-time visualization of HIV-1 GAG trafficking in infected macrophages. - Karine Gousset; Sherimay D Ablan; Lori V Coren; Akira Ono; Ferri Soheilian; Kunio Nagashima; David E Ott; Eric O Freed (PLoS Pathogens)
HIV-1 particle production is driven by the Gag precursor protein Pr55(Gag). Despite significant progress in defining both the viral and cellular determinants of HIV-1 assembly and release, the trafficking pathway used by Gag to reach its site of assembly in the infected cell remains to be elucidated. The Gag trafficking itinerary in primary monocyte-derived macrophages is especially poorly understood. To define the site of assembly and characterize the Gag trafficking pathway in this physiologically relevant cell type, we have made use of the biarsenical-tetracysteine system. A small tetracysteine tag was introduced near the C-terminus of the matrix domain of Gag. The insertion of the tag at this position did not interfere with Gag trafficking, virus assembly or release, particle infectivity, or the kinetics of virus replication. By using this in vivo detection system to visualize Gag trafficking in living macrophages, Gag was observed to accumulate both at the plasma membrane and in an apparently internal compartment that bears markers characteristic of late endosomes or multivesicular bodies. Significantly, the internal Gag rapidly translocated to the junction between the infected macrophages and uninfected T cells following macrophage/T-cell synapse formation. These data indicate that a population of Gag in infected macrophages remains sequestered internally and is presented to uninfected target cells at a virological synapse.